ANÁLISIS DE LA DEDUCCIÓN DE GASTOS POR RESPONSABILIDAD SOCIAL EMPRESARIAL EN EL ORDENAMIENTO PERUANO - Mattos Mena, Grecia Aurora (Revista de Derecho, 2019)
The Peruvian Tax System does not recognize the possibility to deduct from the Income Tax an investment to develop Corporate Social Responsibility. The usual identification of the Corporate Social Responsibility as a philanthropic action could generate complications to deduce those expenses from the Income Tax. Nevertheless, the Peruvian Income Tax Law in its Article 37 regulates the causality principle as a manner to deduce any other expenditure providing that it produces taxable income, or maintain the revenue-producing source. This situation has to be studied in the concrete case. Therefore, this study aims to identify criteria from the Peruvian legal system and its jurisprudence to deduce expenses for Corporate Social Responsibility, in order to avoid unfair repairs.
Keywords: Income tax; deductions; expenditures for Corporate Social Responsibility; causality principle